Dominican Republic : Technical Assistance Report-Balance of Payments Statistics and International Investment Position (April 27-May 1, 2015). - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2018)
This Technical Assistance Report discusses the findings and recommendations made by the IMF mission regarding the balance of payments and international investment position in Dominican Republic. The Central Bank of the Dominican Republic has made considerable progress in disseminating external sector statistics. It will soon disseminate monthly the international reserves and foreign currency liquidity data template to the IMF and data for Table 6 (Gross External Debt Position: by Sector) in the Quarterly External Debt Statistics to the World Bank. Much progress has also been made on the project to compile data on manufacturing services on inputs owned by others.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet